2007
DOI: 10.1097/01.pas.0000213419.08009.b0
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Marginal-zone Lymphoma: One or More Entities? A Histologic, Immunohistochemical, and Molecular Study of 42 Cases

Abstract: We analyzed 42 splenic marginal-zone lymphoma (SMZL) cases diagnosed on splenectomy specimens after established World Health Organization criteria. A predominantly nodular growth pattern was observed in 24 cases; the remainder showed predominantly (11/42) or exclusively (7/42) diffuse infiltration. Twenty-one cases showed the "classic" biphasic appearance; 13 cases exhibited marginal-zone morphology; finally, 8 cases were composed predominantly of small cells. CD21 and CD35 were expressed by 12/42 and 17/38 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 52 publications
1
36
0
2
Order By: Relevance
“…1 Some cytogenetic, molecular and clinical information has been reported previously. 10,13,16,22 The study was conducted in accordance with the Declaration of Helsinki and approved by the local Ethics Committee of each institution.…”
Section: Patient Groupmentioning
confidence: 99%
“…1 Some cytogenetic, molecular and clinical information has been reported previously. 10,13,16,22 The study was conducted in accordance with the Declaration of Helsinki and approved by the local Ethics Committee of each institution.…”
Section: Patient Groupmentioning
confidence: 99%
“…Although earlier reports demonstrated that cells from all SMZL cases had somatic mutations of the IgVH, suggesting that these tumors arise from memory postgerminal center B cells, subsequent studies have revealed a significant molecular heterogeneity [14-16, [25][26][27][28]. In SMZL, as in other B-cell neoplasms, the IgVH mutational status does not play a diagnostic role but has provided insights in the pathogenesis of the disease.…”
Section: Editorialmentioning
confidence: 99%
“…In the case of one subtype of AML, acute promyelocytic leukemia (APL; FAB M3), differentiation can be induced by all-trans retinoic acid (ATRA), a treatment that is curative for many acute promyelocytic leukemia patients. 1,2 However, ATRA has not proven to be effective in the treatment of other subtypes of AML, underscoring the need to identify new compounds that can either induce differentiation as monotherapies or enhance the efficacy of ATRA therapy. Here we report that the tyrosine kinase inhibitor gefitinib markedly enhances ATRA-induced differentiation in myeloid cell lines.…”
Section: Letters To the Editormentioning
confidence: 99%
“…For example, 1/3 of SMZL cases exhibit unmutated immunoglobulin variable heavy-chain (IgVH) genes, with a heterogeneous usage of VH segments. 2 In contrast, IgVH somatic mutations are frequent with a predominance of VH3 usage in LPL patients. 3 But, it is worthnoting that these results are not fully conclusive because they have been obtained on heterogeneous biological materials and in different separated series.…”
mentioning
confidence: 99%